2019
DOI: 10.1002/mnfr.201801427
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Impact Goblet Cell Responses to Lactic Acid Bacteria After Exposure to Inflammatory Cytokines and Mucus Disruptors

Abstract: Scope Mucus produced by goblet cells contributes to gut barrier function. Lactic acid bacteria (LAB) have been shown to impact mucus production. It is not completely known whether mucus production is influenced by the abundantly present fibroblasts in the intestine. Methods and results The influence of fibroblasts on mucus‐related genes including mucin‐2 (MUC2), trefoil factor 3 (TFF3), resistin‐like molecule β (RETNLB), carbohydrate sulfotransferase 5 (CHST5), and galactose‐3‐O‐sulfotransferase 2 (GAL3ST2) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The reason for choosing this cell type and not other commonly used epithelial cell lines such as Caco2 is that LS174T cells are highly secretory and exhibit more of a clear intestinal mucus secreting goblet‐cell phenotype. For that reason it is widely used in goblet cell function studies . Non‐transformed mucin‐producing intestine epithelial cells could be a better choice but are to the best of our knowledge not available yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for choosing this cell type and not other commonly used epithelial cell lines such as Caco2 is that LS174T cells are highly secretory and exhibit more of a clear intestinal mucus secreting goblet‐cell phenotype. For that reason it is widely used in goblet cell function studies . Non‐transformed mucin‐producing intestine epithelial cells could be a better choice but are to the best of our knowledge not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason it is widely used in goblet cell function studies. [38,40,43] Nontransformed mucin-producing intestine epithelial cells could be a better choice but are to the best of our knowledge not available yet. LS174T is also favored because it expresses all the tested genes under homeostatic condition, proinflammatory condition, and ER-stress, [38] which allows studying of the effects of individual hMOs under pro-inflammatory or other diseased conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that goblet cells in the intestine mainly secrete mucins, which, as an important part of the intestinal mucus layer and intestinal epithelial cells, can not only lubricate and protect the intestinal mucosal epithelium Ren et al, 2019), but are also involved in intercellular signalling transduction and the regulation of intestinal mucosa‐associated immune factors (Castagnoli et al, 2021), which can be divided into the secreted mucins and the membrane‐bound mucins according to their existing forms (Etzold & Juge, 2014). It has been shown that bacterial products and their inflammatory factors can induce the formation of sulphonyltransferase, thus making MUC2 sulphate (Ren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that goblet cells in the intestine mainly secrete mucins, which, as an important part of the intestinal mucus layer and intestinal epithelial cells, can not only lubricate and protect the intestinal mucosal epithelium Ren et al, 2019), but are also involved in intercellular signalling transduction and the regulation of intestinal mucosa‐associated immune factors (Castagnoli et al, 2021), which can be divided into the secreted mucins and the membrane‐bound mucins according to their existing forms (Etzold & Juge, 2014). It has been shown that bacterial products and their inflammatory factors can induce the formation of sulphonyltransferase, thus making MUC2 sulphate (Ren et al, 2019). However, when animals are infected with specific pathogens, the goblet cells hyperplasia is often accompanied with alterations in mucin terminal sugar residues, which increases sialylated MUC2 (Grondin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation